2016
DOI: 10.1016/j.vhri.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Patients with HIV/AIDS in Bogotá, Colombia

Abstract: The HRQOL scores of patients with HIV/AIDS receiving antiretroviral therapy were relatively high in Bogotá, Colombia, using the EuroQol questionnaire. The utility data could be useful, in combination with cost data, for future economic evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
5
15
2
4
Order By: Relevance
“…It is paramount for individuals living with HIV to adhere to the ART treatment, as these individuals could live long and healthy lives [5][6][7] . This is in line with previous research that showed that Colombian HIV patients receiving ART had relatively high health utilities 8 . Strict lifelong therapy adherence and optimal medication adherence is needed to guarantee the treatment's success 9,10 .…”
Section: Introductionsupporting
confidence: 92%
“…It is paramount for individuals living with HIV to adhere to the ART treatment, as these individuals could live long and healthy lives [5][6][7] . This is in line with previous research that showed that Colombian HIV patients receiving ART had relatively high health utilities 8 . Strict lifelong therapy adherence and optimal medication adherence is needed to guarantee the treatment's success 9,10 .…”
Section: Introductionsupporting
confidence: 92%
“…Literature shows a number of factors associated with a low mean score of QOL in PLWHA including older age, low income, unemployment, low education, hospitalization due to HIV, and a CD4+ cell count <200 mm 3 19–21. However, little is known about the link between other sociodemographic variables such as the history of incarceration, drug abuse, and stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported population estimates of Hrqol in Colombia, but for patient populations affected by or being treated for chronic diseases (9)(10)(11)(12). Few of these studies have reported Hrqol normative data for the general population (13)(14)(15).…”
mentioning
confidence: 99%